2021
DOI: 10.1192/bjb.2021.50
|View full text |Cite
|
Sign up to set email alerts
|

Teaching trainee psychiatrists a Mentalization-Based Treatment approach to personality disorder: effect on attitudes

Abstract: Aims and method To evaluate whether a brief training using a Mentalization-Based Treatment (MBT) model improves attitudes of trainee psychiatrists working with patients with personality disorder. Trainee psychiatrists (n = 49) completed the Attitudes to Personality Disorder Questionnaire before and after a training consisting of two 3 h lectures on (a) theory of personality disorder and (b) practical skills using an MBT role-play. Results There was a significant improvement on composite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…According to the authors, this was possibly due to a ceiling effect. Finally, Lee et al's (2022) study with a pretest‐posttest design found that brief training improved the attitudes of trainee psychiatrists towards patients with personality disorders to a small to moderate degree. The training consisted of theory on personality disorders and MBT, combined with practicing MBT‐skills using role‐play.…”
Section: Resultsmentioning
confidence: 99%
“…According to the authors, this was possibly due to a ceiling effect. Finally, Lee et al's (2022) study with a pretest‐posttest design found that brief training improved the attitudes of trainee psychiatrists towards patients with personality disorders to a small to moderate degree. The training consisted of theory on personality disorders and MBT, combined with practicing MBT‐skills using role‐play.…”
Section: Resultsmentioning
confidence: 99%